Phonological Metathesis in Iraqi Arabic Dialect: A Synchronic Perspective (Journal of the College of Languages (JCL), 2013)
Phonological metathesis can be defined as an alternation in the normal sequence of two sounds under certain conditions. The present paper is intended to give a detailed synchronic description of phonological metathesis in Iraqi Arabic dialect. For data collection, the researchers have adopted two naturalistic techniques, viz., observation and notes taking. A synchronic analysis is carried out to provide some evidence that describe the sequential change of phonological metathesis in the dialect under investigation. Such sequential changes of metathesized sounds are presented and tabulated. The study concludes with the following finding that this process is not limited to cases where two consonant sounds are transposed, but three consonant sounds can be transposed as well. It has been found that metathesis is frequently involving two adjacent and non-adjacent consonant sounds. And this phonological process does not serve any grammatical function in Iraqi Arabic. As a result, it is an abrupt and sporadic process rather than being gradual and regular. Both Iraqi Arabic sonorants and obstruents undergo the process of phonological metathesis with relatively significant differences.